Liquid|Liquid Interfacial Photoelectrochemistry of Chromoionophore I Immobilised in 4‐(3‐Phenylpropyl)Pyridine Microdroplets. Issue 2 (7th October 2013) - Bartlett, Thomas R.; Ahmed, Safeer; Tuna, Floriana; Collison, David; Blanchard, Gary J.; Marken, Frank
Abstract Photoelectrochemical processes are investigated for chromoionophore I (ETH 5294) dissolved in 4‐(3‐phenylpropyl)pyridine (PPP) and deposited in the form of a microdroplet array (through evaporation deposition from a solution in acetonitrile) onto a 5 mm diameter basal plane pyrolytic graphite (BPPG) electrode. Stable biphasic dark voltammetric responses (two electron/two proton) are observed in phosphate buffer solution (from pH 2 to 12) with a switch in reactivity at pH 5 due to a biphasic protonation step. The photoelectrochemical activity at pH 2 is investigated further by phototransient amperometry. The protonated chromoionophore I is shown to be the photoactive component (supported by EPR data) and "hole transfer" at the liquid|liquid interface to aqueous oxalate is demonstrated. This interfacial hole‐transfer process can be "switched off" by hydrophobic anions (PF6−), which compete for cationic liquid|liquid PPP surface binding sites. Implications for light harvesting and liquid semiconductor properties are discussed.